A new species of Ontherus Erichson, 1847 (Coleoptera: Scarabaeidae: Scarabaeinae: Coprini) and new distributional records of Cryptocanthon humidus Howden, 1973 (Coleoptera: Scarabaeidae: Scarabaeinae: Deltochilini) for Ecuador - Chamorro, William; Lopera-Toro, Alejandro; Génier, François (Zootaxa, 2024)
A new species of Ontherus Erichson, 1847 (Coleoptera: Scarabaeidae: Scarabaeinae: Coprini) from Loja province (southern Ecuador) is described. The new species is putatively assigned to the subgenus Ontherus. An updated identification key is provided for the Ecuadorian species of Ontherus. Additionally, Cryptocanthon humidus Howden, 1973 (Coleoptera: Scarabaeidae: Scarabaeinae: Deltochilini) is registered for the first time in Ecuador.